Prospects of Potassium and Phosphate Solubilizing Bacteria for Nodulation Enhancement, growth and yield of Chickpea plant (Cicer arientinum L.) - Kwestan Jawhar Mustafa; Aras.M. Khudhur (Zanco Journal of Pure and Applied Sciences, 2020)
Seventy one percent of the overall P and K in Erbil governorate soils are in inorganic forms which are unavailable for use in plants. As a result, chemical fertilizer is often used to supplement the nutrient for the growth crops. To reduce the addition of chemical fertilizer to agricultural soils, this research has been conducted to isolate naturally occurring potassium solubilizing microorganisms (KSB) and phosphate solubilizing microorganisms (PSB) from Erbil soil samples and use to improve chickpea growth. Thirty nine efficient PSB isolates were selected based on their ability to clear zone formation on Pikovskaya´s agar medium of and 26 efficient KSB isolates using Aleksandro medium. Depending on microscopical, cultural, and biochemical characteristics, PSB strains belonged to Ps.putida while KSB strains referred to B.circulans. All PSB and KSB strains were screened for their solubilization efficiency on both solid and liquid medium. Bh36 strain of Ps.Putida was the most efficient isolate in P solubilization (94.92%,117.78mg/ml) and the most efficient B.circulans strain in K solubilization was Q1 (87.01%,4.81mg/ml), and they were used for P and K biofertilizers preparation, respectively. Pot experiment showed that seed inoculation with Ps.Putida, B.circulans, and combined (Ps.Putida+ B.circulans) application significantly enhanced chickpea growth. Combined (Ps.Putida+ B.circulans) inoculation recorded the highest increase in shoot height (46.29cm), root length (37.84cm), shoot dry weight (4.28g/plant), number of seed (26.37seeds/plant), number of active nodules (11.56/plant) P (6.35g/plant) and K uptake (65.75g/plant), soil available phosphorus (17.21mg/kg) and soil available potassium (314.5mg/kg). It could be assumed that local Ps.Putida and B.circulans strain can be used as biofertilizer of P and K to improve plant growth and soil fertility.